Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)

Dye sensitized solar cell (DSSC) by a novel fully room temperature process: a solar paint for smart windows and flexible substrates - Agarkar, Shruti A.; Dhas, Vivek V.; Muduli, Subas; Ogale, Satishchandra B. (RSC Advances, 2012)
We report the development of a titania-nanoparticle-based solar paint which gives a conversion efficiency of 3.6% on FTO/glass substrates under fully room temperature processing. The paint cures quickly saving time in the cell fabrication process. Even on a flexible ITO/PET substrate efficiency of 2.4% was achieved. We present and analyze the results of described materials and device property characterizations.

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

Toward a quantitative correlation between microstructure and DSSC efficiency: a case study of TiO2-xNx nanoparticles in a disordered mesoporous framework - Sivaranjani, Kumarsrinivasan; Agarkar, Shruti A.; Ogale, Satishchandra B.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
The efficiency (eta) of a dye-sensitized solar cell (DSSC) depends on various parameters, the critical factors being a fast charge carrier transport and a slow rate of electron-hole recombination. The present article describes a simple combustion synthesis method to prepare TiO2-xNx with following four important features that directly influences eta: (1) a disordered mesoporous structural framework with high surface area to give high dye-loading and a small diffusion length for charge carriers allowing rapid movement to the surface; (2) electrically interconnected nanocrystalline TiO2-xNx particles with good necking and predominant (101) anatase facets to minimize electron-hole recombination; (3) low charge storage capacity in the titania framework; and (4) surface unsaturation assisting all the above factors. The pseudo-three-dimensional nature of mesoporous TiO2-xNx with the above features demonstrates the importance of textural features, and porosity allows faster diffusion of charge carriers to surface and their utilization to generate power. A quantitative correlation between interconnected nanoparticles over larger distances in a mesoporous framework and eta is demonstrated. This study also demonstrates an inexpensive and rapid method of producing the photoanode material with high eta in about 10 min.

Comparative study on the dye sensitized solar cell performance of solution processed ZnO - Jana, Arpita; Das, Partha Pratim; Agarkar, Shruti A.; Devi, P. Sujatha (Solar Energy, 2014)
We have monitored the performance of the dye-sensitized solar cells (DSSC) using solution processed ZnO having different shapes and aspect ratios. The aspect ratio and surface area of the ZnO structures have been regulated by carefully controlling the precursor concentration and reaction conditions. The shape of the synthesized structures has been varied from larger rods to smaller rods to hexagonal prisms. The synthesized hexagonal prism shaped ZnO with an aspect ratio of around one exhibited the highest surface area of 42 m(2)/g. The ZnO rods with higher aspect ratios of 5 and 16 exhibited lower surface areas of 22 and 2 m(2)/g, respectively. The dye sensitized solar cells constructed using the as-prepared ZnO structures and N719 dye molecules, exhibited efficiencies that varied as a function of surface area of the samples, with ZnO hexagonal prism exhibiting a maximum efficiency of around 1.38 +/- 0.01%. The results indicated a direct correlation between the surface area of the ZnO structures and the energy conversion efficiency. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DSSC; Photoanode; surface area; ZnO

Defects in chemically synthesized and thermally processed ZnO nanorods: implications for active layer properties in dye-sensitized solar cells - Das, Partha Pratim; Agarkar, Shruti A.; Mukhopadhyay, Soumita; Manju, Unnikrishnan; Ogale, Satishchandra B.; Devi, P. Sujatha (Inorganic Chemistry, 2014)
We have carried out the effect of post annealing temperatures on the performance of solution-grown ZnO rods as photoanodes in dye-sensitized solar cells. Keeping our basic objective of exploring the effect of native defects on the performance of DSSC, we have synthesized ZnO rods having length in the range of 2-5 mu m by a modified sonication-induced precipitation technique. We performed extensive characterization on the samples annealed at various temperatures and confirmed that annealing at 300 degrees C results in ZnO rods with minimum native defects that have been identified as doubly ionized oxygen vacancies. The electron paramagnetic resonance measurements on the samples, on the other hand, confirmed the presence of shallow donors in the low temperature annealed samples. We also carried out electrochemical impedance measurements to understand the transport properties at different interfaces in the solar cell assembly. We could conclude that solution-processed ZnO rods annealed at 300 degrees C are better suited for fabricating DSSC with improved efficiency (1.57%), current density (5.11 mA/cm(2)), and fill factor (45.29%). On the basis of our results, we were able to establish a close connection between the defects in the metal oxide electron transporting nano system and the DSSC performance.

Electronically and catalytically functional carbon cloth as a permeable and flexible counter electrode for dye sensitized solar cell - Tathavadekar, Mukta; Biswal, Mandakini; Agarkar, Shruti A.; Giribabu, Lingamallu; Ogale, Satishchandra (Electrochimica Acta, 2014)
In this work we demonstrate that a conducting carbon cloth obtained by one-step pyrolysis of easily available cellulose fabric competes favorably with the commonly employed expensive platinum/FTO system as a counter electrode for dye sensitized solar cell (DSSC). In view of the low carbonization temperature (1000 degrees C) which forbids full graphitization, the nature of carbon in this case is represented by topologically randomly assembled nanoscale graphene units (turbostratic carbon). This morphology has high density of edge states and oxygen containing surface groups rendering multitude of catalytic sites for the reduction of I-3(-). Moreover the cloth is permeable to the dye and/or liquid electrolyte and its absorption properties also help retain the electrolyte. A fairly high efficiency of 5.8% is achieved using such cloth as a counter electrode as against 7% with the conventional Pt/FTO system. Moreover, the permeable property of the cloth eliminates a complete step of drilling hard TCO substrates for final dispensing of electrolyte into the device and the sealing process is also facile. In fact even the dye can be dispensed through the cloth. Finally, the flexibility of the carbon cloth can adapt easily to flexible/wearable DSSC designs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: conducting carbon cloth; counter electrode; DSSC; without drilling

Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte

Nanophase CulnS(2) nanosheets/CuS composite grown by the SILAR method leads to high performance as a counter electrode in dye sensitized solar cells - Bhosale, Reshma K.; Agarkar, Shruti A.; Agrawal, Ishita; Naphade, Rounak A.; Ogale, Satishchandra (RSC Advances, 2014)
Single phase CulnS(2) (CIS) nanosheets are synthesized on TiO2 coated FTO by the simple technique of Successive Ionic Layer Adsorption Reaction (SILAR) followed by annealing at 500 degrees C. Annealing at a lower temperature of 250 degrees C is found to yield CuS nanoparticles in addition to the CIS phase. Both single phase CIS and the CuS/CIS nanocomposite were examined as counter electrodes for a dye-sensitized solar cell (DSSC). The CIS-CuS composite is found to have a synergistic effect on the catalytic performance toward the reduction of tri-iodide, yielding a power conversion efficiency of 6.3% as compared to pristine CIS (5%) or CuS (3.5%). The possible reasons behind the high performance of the composite are elucidated using cyclic voltammetry (CV) measurements and electrochemical impedance spectroscopy (EIS).

Nickel cobalt sulfide nanoneedle array as an effective alternative to pt as a counter electrode in dye sensitized solar cells - Banerjee, Abhik; Upadhyay, Kush Kumar; Bhatnagar, Sumit; Tathavadekar, Mukta; Bansode, Umesh P.; Agarkar, Shruti A.; Ogale, Satishchandra B. (RSC Advances, 2014)
Self supported nickel cobalt sulfide (NCS) nanoneedles are directly formed on FTO glass substrates by sulphurization of nickel cobalt oxide nanoneedles (grown by a hydrothermal method) in the presence of a hydrogen sulfide and argon gas mixture. These NCS nanoneedles when used as a counter electrode for dye sensitized solar cells (DSSCs) show efficient catalytic activity towards the I-/I-3(-) redox couple, and lead to an impressive efficiency of 6.9%, compared with 7.7% obtained with a Pt electrode in similarly constructed devices.

Novel precursors for anatase nanorods and their application in DSSCs - Mishra, Biswajit; Agarkar, Shruti A.; Khushalani, Deepa (Materials Chemistry and Physics, 2014)
Syntheses for the formation of two new precursors for TiO2 nanorods: titanium propanediolate and titanium erythritolate, have been detailed. These precursors have a rod like morphology and have been found to have higher thermal stability than commercially available precursors. The conversion of the precursors to anatase phase of TiO2 involves a simple heating protocol and importantly the morphology is conserved. The resulting anatase nanorods have been characterised and evaluated as photoanodes in dye sensitized solar cells (DSSCs). Overall device efficiencies of 3.2% and 2.3% were achieved when anatase rods (obtained from titanium propanediolate and titanium erythritolate respectively) were used. These values are higher than the 1.1% efficiency obtained from the control device (made with spherical anatase nanoparticles). It is found that forming ordered 1-D rods leads to enhanced charge transport and charge collection at the electrode along with a commensurate decrease in charge recombination. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Nanostructures; Non-crystalline materials; Sol-gel growth

Synthetic precursor to vertical TiO2 nanowires - Mishra, Biswajit; Ghildiyal, P.; Agarkar, Shruti A.; Khushalani, Deepa (Materials Research Express, 2014)
An easy protocol for improvement in formation of the photoanode in a dye sensitized solar cell is addressed. Specifically, a novel synthesis for the formation of a TiO2 precursor: titanium butanediolate, is detailed. This precursor is found to have higher thermal and temporal stability than commercially available TiO2 precursors and it has successfully been employed in the one-pot synthesis of rutile nanowires grown directly on a conducting substrate: fluorine doped tin oxide (FTO). This synthesis has been further extended to directly form a mixed phase TiO2 film consisting of rutile nanowires along with anatase spherical particles on FTO and this assembly has been used as the photoanode in a dye-sensitized solar cell. The synergistic effect of the two phases has provided a net DSSC efficiency of 4.61% with FF = 61%.
Keywords: Nanomaterials; Nanowires; TiO2

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads

Hybrid perovskite films by a new variant of pulsed excimer laser deposition: a room-temperature dry process - Bansode, Umesh P.; Naphade, Rounak; Game, Onkar S.; Agarkar, Shruti A.; Ogale, Satishchandra (Journal of Physical Chemistry C, 2015)
A new variant of the classic pulsed laser deposition (PLD) process is introduced as a room-temperature dry process for the growth and stoichiometry control of hybrid perovskite films through the use of nonstoichiometric single target ablation and off-axis growth. Mixed halide hybrid perovskite films nominally represented by CH(3)NH(3)PbI(3-x)A(x) (A = Cl or F) are also grown and are shown to reveal interesting trends in the optical properties and photoresponse. Growth of good quality lead-free CH3NH3SnI3 films is also demonstrated, and the corresponding optical properties are presented. Finally, perovskite solar cells fabricated at room temperature (which makes the process adaptable to flexible substrates) are shown to yield a conversion efficiency of about 7.7%.

Photochemical performance of ZnO nanostructures in dye sensitized solar cells - Das, Partha Pratim; Mukhopadhyay, Soumita; Agarkar, Shruti A.; Jana, Arpita; Devi, P. Sujatha (Solid State Sciences, 2015)
In this work, the photoconversion efficiencies of ZnO having diverse microstructures and structural defects have been investigated. A conversion efficiency of 138% was achieved for the DSSCs fabricated with as prepared ZnO nanorods having minimum vacancy defects and a favourable one dimensional directional pathway for electron conduction. The DSSCs fabricated with ZnO nanoparticles exhibited relatively low conversion efficiency of 1.004% probably due to multiple trapping/detrapping phenomena within the grain boundaries and ZnO flowers though exhibited a high dye adsorption capability exhibited the lowest conversion efficiency of 0.59% due to a high concentration of structural defects. Based on the experimental evidences, we believe that the type of defects and their concentrations are more important than shape in controlling the overall performance of ZnO based DSSCs. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: DSSC; Efficiency; Emission; Structural defects; ZnO